Near-zero metamaterial inspired UHF antenna for nanosatellite communication system - Alam, Touhidul (2019)
Epsilon-and-mu-near-zero (EMNZ) metamaterial structure inspired UHF antenna for nanosatellite has been proposed in this paper. The antenna consists of 3 × 2-unit cell array on the ground plane and a meander line radiating patch. Coaxial probe feeding technique has been obtained to excite the antenna. The meander line enables the antenna to resonate at lower UHF band and the metamaterial array is used to make the resonant frequency stable by reducing the coupling effect with metallic nanosatellite structure. The metamaterial structure exhibits EMNZ characteristics from 385 MHz to 488.5 MHz, which facilitates stable resonant frequency and higher antenna efficiency when embedded with nanosatellite structure. The proposed EMNZ inspired antenna has achieved measured impedance bandwidth (S11 < −10 dB) of 14.92 MHz (391 MHz–405.92 MHz). The perceptible novelty of this paper is the development of EMNZ metamaterial that significantly improves the UHF antenna’s operating frequency stability as well as efficiency for low earth orbit nanosatellite communications.